2009
DOI: 10.1371/journal.pone.0008420
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Signaling Events That Impact Classical Nuclear Import and Target Nuclear Transport Factors

Abstract: BackgroundSignaling through MEK→ERK1/2 and PI3 kinases is implicated in many aspects of cell physiology, including the survival of oxidant exposure. Oxidants play a role in numerous physiological and pathophysiological processes, many of which rely on transport in and out of the nucleus. However, how oxidative stress impacts nuclear trafficking is not well defined.Methodology/Principal FindingsTo better understand the effect of stress on nucleocytoplasmic trafficking, we exposed cells to the oxidant diethyl ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…It remains equally enigmatic why components of its own pathway, as well as CAS and possibly other members of the nuclear translocation machinery, are modified by Urm1. Nuclear translocation is halted on exposure to oxidants (39). Urmylation of CAS could contribute to an arrest in nuclear transport (e.g., by decreasing the pool of cytosolic importin α).…”
Section: Discussionmentioning
confidence: 99%
“…It remains equally enigmatic why components of its own pathway, as well as CAS and possibly other members of the nuclear translocation machinery, are modified by Urm1. Nuclear translocation is halted on exposure to oxidants (39). Urmylation of CAS could contribute to an arrest in nuclear transport (e.g., by decreasing the pool of cytosolic importin α).…”
Section: Discussionmentioning
confidence: 99%
“…We performed similar immunoblot analyses with other ROS, including menadione, an oxidative agent like H 2 O 2 , and diethylmaleate, a sulfhydryl-reactive agent that has been shown to affect nucleocytoplasmic transport (Crampton et al, 2009;Kodiha et al, 2009;Kodiha et al, 2008;Matsuura and Stewart, 2004;Sato et al, 1993). These reagents also increased the intracellular ROS level as measured by the fluorescent probe (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…This implies that oxidative stress regulates the efflux via mechanisms other than S-S bond formation. Previous studies have demonstrated that Nups 214, 153, 98, 88 and 62 are phosphorylated and/or glycosylated by oxidative stress (Crampton et al, 2009;Kodiha et al, 2009). Other studies have reported that the Nup214/Nup88 complex and Nup98 are involved in export but not in import (Hutten and Kehlenbach, 2006;Oka et al, 2010).…”
Section: Nup Positioning Within the Npc And S-s Bond Formationmentioning
confidence: 98%
See 2 more Smart Citations